Sociocultural and Economic Factors Influencing JKN Participation: A Cross-Sectional Study in Bajoe, Indonesia - Ashari, Muhammad Rizki; Arwan; Syam, Sadli (Indonesian Scientific Publication, 2024)
The implementation of the Jaminan Kesehatan Nasional (JKN) program in Indonesia seeks to achieve Universal Health Coverage by ensuring equitable access to health services for all citizens. Despite this aim, disparities in participation persist, particularly in rural and coastal regions. This study aimed to analyze the factors influencing community participation in the JKN program within the working area of Bajoe Community Health Center, Bone Regency. A cross sectional quantitative approach was used to survey 291 respondents selected through purposive sampling. Structured questionnaires were administered to assess demographic characteristics and the influence of five key variables: knowledge, trust, income, health condition, and family support. Data were analyzed using univariate and bivariate (Chi square) statistical techniques. Results revealed that knowledge, trust in the JKN system, income level, and family support had statistically significant associations with program participation (p < 0.05). Specifically, individuals with better knowledge, higher trust, greater income, and supportive families were more likely to be enrolled. Conversely, perceived or actual health status showed no significant correlation with participation. These findings suggest that proactive enrollment behavior is influenced more by informational, economic, and social dynamics than by immediate health needs. The study concludes that increasing JKN participation requires multi-dimensional strategies, including culturally tailored public education, institutional trust building, improved subsidy access for low income households, and family centered outreach. These interventions are essential to bridge participation gaps and strengthen the national health insurance framework.